Differences in bone mineral density of trajectory between lumbar cortical and traditional pedicle screws - Renjie Zhang; Hai Gao; Huimin Li; Tao Xing; Chongyu Jia; Jianxiang Zhang; Fulong Dong; Cailiang Shen (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Cortical bone trajectory (CBT) has been well-known in spine surgery for obtaining improved fixation while minimizing soft tissue dissection. This study was designed to compare the bone mineral density (BMD) between the CBT and traditional trajectory (TT) by using Hounsfield unit (HU) values and identify the ideal decades of patients and the suitable lumbar segments using this CBT technology from a radiological standpoint. Methods Patients were selected randomly from an institutional database based on age (evenly distributed by a decade of life) and gender. A total of 240 healthy patients had a computed tomography (CT) scan of the chest, abdomen, and pelvis. For each patient, axial slices of every vertebra were cut in two planes: one horizontal to the pedicle representing the plane wherein pedicle screws were inserted using the TT and the other in a caudocranial plane representing the plane wherein pedicle screws were inserted using the CBT. For each trajectory, a region of interest (ROI) was selected within the area wherein the screws were inserted. A CT number (HU values) was then calculated within each ROI to represent bone density. Results HU values measured at the ROI of CBT were significantly greater than those of the traditional pedicle screw in all age groups, and the specific value (ratio of the HU values of CBT/the HU values of TT) between CBT and TT was 1.92. A significant difference was observed between male and female. The HU values of CBT and TT of males were generally higher than those of females (males: CBT/TT 1.89 ± 0.45; Females: CBT/TT 1.95 ± 0.47). The specific value in HU values significantly increased with increasing age (p = 0.000) and cauda lumbar level (p = 0.000) in males and females. Conclusion BMD, as measured by HU values for the ROI of the CBT screw, was significantly greater than that of the traditional pedicle screw, especially in old patients and cauda lumbar segments.